Analisis Faktor Panjang Jalan, Distribusi Listrik, Jumlah Penduduk Dan Penanaman Modal Asing Terhadap PDRB Di Indonesia - Rifki Khoirudin (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2022)
This research has a goal or focus on the productivity of a country. This review is carried out because the government is intensively carrying out development, investment and human resource development on a national scale, therefore the author wants to know the impact or influence caused by road length, electricity distribution, population and foreign investment. The research methodology used is descriptive quantitative research and data collection methods by means of documentation from the government's official website. After that, the data was processed using the Stata application with the panel data regression method. Case studies of 34 provinces in Indonesia. The result of this research is that road infrastructure has no influence and is negatively related. While the other three variables have a positive and significant effect.